2009
DOI: 10.1073/pnas.0904847106
|View full text |Cite
|
Sign up to set email alerts
|

Human gut microbiome adopts an alternative state following small bowel transplantation

Abstract: Small bowel transplants provide an exceptional opportunity for long-term study of the microbial ecology of the human small bowel. The ileostomy created at time of transplant for ongoing monitoring of the allograft provides access to samples of ileal effluent and mucosal biopsies. In this study, we used qPCR to assay the bacterial population of the small bowel lumen of 17 small bowel transplant patients over time. Surprisingly, the posttransplant microbial community was found to be dominated by Lactobacilli and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
204
4
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(236 citation statements)
references
References 34 publications
12
204
4
3
Order By: Relevance
“…However, we observed a large proportion of anaerobes from the Clostridium cluster XIVa in our effluent samples, such as Coprococcus eutactus and relatives, which was detected up to 6% of the total community. Therefore, our data do not confirm a recent study that concluded oxygen exposure to have a major impact at the end of the terminal ileum in ileostomy patients (Hartman et al, 2009). Although we cannot fully exclude a potential role of oxygen, we consider it more likely that the absence of a colonic reflux explains our observations.…”
Section: Ecological Model Of the Small Intestinal Microbiotacontrasting
confidence: 99%
See 2 more Smart Citations
“…However, we observed a large proportion of anaerobes from the Clostridium cluster XIVa in our effluent samples, such as Coprococcus eutactus and relatives, which was detected up to 6% of the total community. Therefore, our data do not confirm a recent study that concluded oxygen exposure to have a major impact at the end of the terminal ileum in ileostomy patients (Hartman et al, 2009). Although we cannot fully exclude a potential role of oxygen, we consider it more likely that the absence of a colonic reflux explains our observations.…”
Section: Ecological Model Of the Small Intestinal Microbiotacontrasting
confidence: 99%
“…146 Mb of sequence information could be assembled into contigs that collectively encompass 63 Mb, with the largest contig being 78 kb, and leaving only 13% of the sequence-reads unassembled. This assembled proportion of sequences is considerably higher than previously observed with fecal metagenomes (Gill et al, 2006;Kurokawa et al, 2007), indicating a lower species diversity in the small intestine as compared with the colon, which is in line with the previous observations based on 16S rRNA genes (Hartman et al, 2009;Booijink et al, 2010). More than 170 000 genes could be assigned in the assembled contigs, of which 16% was complete.…”
Section: Microbiome Of Small Intestine Is Less Complex Than That Of Tsupporting
confidence: 88%
See 1 more Smart Citation
“…Although phylogenetic coherence has previously been demonstrated for habitat preference at the class level (48,49) and genome size at the order level (50), we show that there are phylogenetically coherent pulse-response niches among cohabiting microorganisms. The high degree of phylogenetic coherence may reflect the complexity of survival of and resuscitation from desiccation.…”
Section: Discussioncontrasting
confidence: 63%
“…There is also one report of there being differences in mucosal oxygen concentration along the human colon, especially between the caecum and distal regions (pO 2 [mm Hg] being 33.7 ± 7.5 in the caecum, compared with 40.7 ± 8.2, 41.2 ± 8.7 and 39.7 ± 7.3 for the transverse colon, sigmoid colon and rectum, respectively (Sheridan et al, 1987)). Interestingly, recent studies linking a higher abundance of aerotolerant bacteria with ileal CD (Baumgart et al, 2007) and surgical intervention (Hartman et al, 2009) suggest that perturbations in oxygen concentration may be associated with the observed dysbiosis. Our findings are not inconsistent with these reports, and collectively, all three studies support the hypothesis that the dysbiosis seen with some types of IBD might initially be in response to the altered oxygenation state of the inflamed tissue.…”
Section: Discussionmentioning
confidence: 99%